Gaining Insights on the Interactions of a Class of Decorated (2‐([2, 2′‐Bipyridin]‐6‐yl)phenyl)platinum Compounds with c‐Myc Oncogene Promoter G‐Quadruplex and Other DNA Structures. Issue 54 (1st August 2022) - Savva, Loukiani; Fossépré, Mathieu; Keramidas, Odysseas; Themistokleous, Alexandros; Rizeq, Natalia; Panagiotou, Nikos; Leclercq, Maxime; Nicolaidou, Eliana; Surin, Mathieu; Hayes, Sophia C.; Georgiades, Savvas N.
Abstract: Organometallic molecules offer some of the most promising scaffolds for interaction with G‐quadruplex nucleic acids. We report the efficient synthesis of a family of organoplatinum(II) complexes, featuring a 2‐([2, 2′‐bipyridin]‐6‐yl)phenyl tridentate (N ∧ N ∧ C) ligand, that incorporates peripheral side‐chains aiming at enhancing and diversifying its interaction capabilities. These include a di‐isopropyl carbamoyl amide, a morpholine ethylenamide, two enantiomeric proline imides and an oxazole. The binding affinities of the Pt‐complexes were evaluated via UV‐vis and fluorescence titrations, against 5 topologically‐distinct DNA structures, including c‐myc G‐quadruplex, two telomeric (22AG) G‐quadruplexes, a duplex (ds26) and a single‐stranded (polyT) DNA. All compounds exhibited binding selectivity in favour of c‐myc, with association constants (Ka ) in the range of 2–5×10 5  M −1, lower affinity for both folds of 22AG and for ds26 and negligible affinity for polyT. Remarkable emission enhancements (up to 200‐fold) upon addition of excess DNA were demonstrated by a subset of the compounds with c‐myc, providing a basis for optical selectivity, since optical response to all other tested DNAs was low. A c‐myc DNA‐melting experiment showed significant stabilizing abilities for all compounds, with the most potent binder, the morpholine‐Pt‐complex, exhibiting a ΔTm >30 °C, at 1 : 5 DNA‐to‐ligand molar ratio. The same study implied contributions of the diverse side‐chains to helix stabilization. To gain direct evidence of the nature of the interactions, mixtures of c‐myc with the four most promising compounds were studied via UV Resonance Raman (UVRR) spectroscopy, which revealed end‐stacking binding mode, combined with interactions of side‐chains with loop nucleobase residues. Docking simulations were conducted to provide insights into the binding modes for the same four Pt‐compounds, suggesting that the binding preference for two alternative orientations of the c‐myc G‐quadruplex thymine 'cap' ('open' vs. 'closed'), as well as the relative contributions to affinity from end‐stacking and H‐bonding, are highly dependent on the nature of the interacting Pt‐complex side‐chain. Abstract : Hooked on c‐myc : A series of organoplatinum(II) compounds with diverse amino‐acid‐inspired side‐chains exhibit high affinity and binding selectivity for the c‐myc G‐quadruplex, along with significant emission enhancement and optical selectivity for this target vs. other DNA topologies. The compounds behave as efficient c‐myc G‐quadruplex stabilizers. Insights on the nature of their interaction with c‐myc were gained via resonance Raman investigation and docking simulation studies, highlighting the importance of the side‐chains for the interaction.